The Invisible Beauty of the Biodiversity: The Rubiaceae Taxon - Valli, M. [UNESP]; Young, M. C. M.; Bolzani, V. S. [UNESP] (Brazilian Chemical Soc, 2016)
The Brazilian Biodiversity is one of the richest in the world, distributed in different biomes, among the most important, are the Cerrado, Atlantic Forest and Amazon Rainforest. It is estimated that these ecosystems are home to about 2 million plants, animals and microorganisms, representing a vast field of research. This immense biological treasure visually fills the beauty of the landscapes that has delighted generations and represents an incalculable molecular wealth, often unnoticed, because they are not visually noticeable. In this paper the beauty of the plant species is highlighted by presenting a formidable beauty, which is not visible to the eyes, the molecules can provide great utility. Thus, the chemistry of metabolites extracted from our biodiversity and especially of plants is fascinating and architecturally beautiful. As a highly sophisticated laboratory, plants produce novel structures that stimulate the creativity of chemists and may be useful as drugs, dietary supplements, cosmetics and agrochemicals. Given the molecular complexity and diversity of the many plant groups, the Rubiaceae family was chosen for this short review, for suitably representing the visible and the invisible beauty of our biodiversity.
Keywords: Rubiaceae; Biodiversity